USE OF INFORMATION TECHNOLOGY IN THE EDUCATIONAL PROCESS AND TRAINING IN CONSTRUCTION DRAWINGS WHEN TEACHING COMPUTER GRAPHICS - Д.Е.ОМОНОВ (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In the age of rapid development of information and communication technologies, information policy is part of cultural policy. Ensuring the full use of information resources by the population, the full interaction of our country with the global information flow in the late 80s and 90s of the last century, the widespread introduction of information and telecommunication technologies initially developed from the period when issues were resolved at the republican level. These are not only scientific and technical information institutions, but also libraries and higher education institutions that have understood the relevance of the republic’s entry into the global information system and are involved in the process of universities’ entry. The development path we have chosen is aimed at the renewal and development of the state and society, taking into account world experience, as well as age-old national traditions, customs, and traditional lifestyles.